Rare Cause of Wide QRS Tachycardia - Nikolay Yu. Mironov; Natalia A. Mironova; Marina A. Saidova; Olga V. Stukalova; Sergey P. Golitsyn (Case Reports in Cardiology)
Cardiac involvement is a well-known feature of neuromuscular diseases. Most commonly cardiac manifestations occur later in the course of the disease. Occasionally severe cardiac disease, including conduction disturbances, life-threatening arrhythmias, and cardiomyopathy, with its impact on prognosis, may be dissociated from peripheral myopathy. We report a case of bundle branch reentrant ventricular tachycardia as primary manifestation of myotonic dystrophy and discuss associated diagnostic and treatment challenges.